A role for glycolipid biosynthesis in severe fever with thrombocytopenia syndrome virus entry. - Mary Jane Drake (PLoS Pathogens, 2017)
A novel bunyavirus was recently found to cause severe febrile illness with high mortality in agricultural regions of China, Japan, and South Korea. This virus, named severe fever with thrombocytopenia syndrome virus (SFTSV), represents a new group within the Phlebovirus genus of the Bunyaviridae. Little is known about the viral entry requirements beyond showing dependence on dynamin and endosomal acidification. A haploid forward genetic screen was performed to identify host cell requirements for SFTSV entry. The screen identified dependence on glucosylceramide synthase (ugcg), the enzyme responsible for initiating de novo glycosphingolipid biosynthesis. Genetic and pharmacological approaches confirmed that UGCG expression and enzymatic activity were required for efficient SFTSV entry. Furthermore, inhibition of UGCG affected a post-internalization stage of SFTSV entry, leading to the accumulation of virus particles in enlarged cytoplasmic structures, suggesting impaired trafficking and/or fusion of viral and host membranes. These findings specify a role for glucosylceramide in SFTSV entry and provide a novel target for antiviral therapies.